Effects of swimming exercise on high-fat diet-induced low bone mineral density and trabecular bone microstructure in rats - Kang, Yun-Seok (J Exerc Nutrition Biochem, 2017)
[PURPOSE]: This study aimed to investigate the effect of swimming exercise on high-fat diet-induced low bone mineral density (BMD) and trabecular bone microstructure in rats. [METHODS]: Eight-week-old male Sprague– Dawley (SD) rats were divided into a normal diet group (n = 9) and a high-fat diet group (n = 15). Three rats in each group were sacrificed after 8 weeks of high-fat diet to evaluate the association between high-fat diet and bone health. The other 18 rats were reassigned to 3 groups (normal diet control, NC; high-fat diet control, HC; high-fat diet + Exercise, HEx) for up to another 8 weeks. Rats in the exercise group were trained for a swimming exercise program (1 h/day, 5 times/ week for 8 weeks). All rats were sacrificed 24 h after the last bout of exercise to analyze the BMD and trabecular bone microstructure in the femur and tibia, using micro-computed tomography. [RESULTS]: First, the effect of high-fat diet on bone health was examined. It was observed that BMD, percent bone volume (BV/TV), and trabecular number (Tb.N) of the femur and tibia were lower in rats in the high-fat diet group than in those in the normal diet group (p < .05). In addition, BMD, BV/TV, and Tb.N of the femur and tibia were significantly increased in rats that underwent the 8-week swimming exercise program, compared to the corresponding values in rats in the HC group (p < .05). [CONCLUSION]: These results indicate that high-fat diets negatively affect bone health; however, these negative effects can be improved by exercises such as swimming.